Promote mentor-mentee relationships among academics - Leow, Serena Wai Yee *; Long, Chiau Ming * (New Straits Times Press (M) Bhd., 2024)
LETTERS: RECENT concerns about the publication of substandard research articles by Malaysian academics has heightened the concerns about the quality of higher education and academicians in the country. A contributing factor is insufficient mentorship between seasoned and emerging scholars. Most individuals who enter into the world of academia perceive teaching as the primary role of the profession. However, the challenging reality of publish or perish sinks in, a task for which early-career researchers are often inadequately prepared. Mentorship plays an important role in sustaining knowledge creation and professional growth of academics towards strengthening and enhancing research quality.